Industrial training report: PRISM Integrated Sdn Bhd / Muhammad Faiz Afiq Mohd Yusof - Mohd Yusof, Muhammad Faiz Afiq (Perpustakaan Tengku Anis, 2017)
Abstract: Industrial training is the place exposed the trainee to the real working environment. The application of knowledge, skills and experience during internships helps trainee to gain more knowledge than the knowledge during their study in university. Trainee gained some knowledge based on the training activities during internship as well as learns the soft skills needed in working environment. The service offer quality it also will help to increase customer satisfaction. So, this chapter is explain about; Chapter 1: Introduction (Background of the organization), Chapter 2: Organizational Information, Chapter 3: Industrial Training Activities and Special Projects and Chapter 4: Conclusions (Umitations and Recommendations by) the Prism Integrated Sdn Bhd.